A novel protocol for occlusal splint adjustment to treat TMD in sleep bruxism - Giannasi, Lilian Christyane [UNESP]; Hirata, Raquel Pastréllo; Politti, Fabiano; Nacif, Sergio Roberto; Leitão Filho, Fernando Sérgio Studart; Oliveira, Luis Vicente Franco De (Pontifícia Universidade Católica do Paraná, 2012)
INTRODUCTION: Sleep bruxism (SB) is a stereotypical movement disorder that is characterized by rhythmic masticatory muscle activity associated with tooth grinding and occasional jaw clenching. OBJECTIVES: The aim of this study was to determine the relief time for temporomandibular disorders (TMD), cervical and otological signs and symptoms in patients with BS treated with occlusal splints (OS) for a period of 180 days. MATERIALS AND METHODS: Thirty patients, between ages 22 and 53 years old, presenting SB and TMD, including cervical and otological symptoms, were enrolled in this study. The patient’s treatment protocol consisted of using the OS applying a novel adjustment protocol. The total follow-up period was 180 days. The paired Student t-test was used to compare before and after long-term OS treatment. RESULTS: For all variables, the results were statistically significant (p < 0.001). As to the TMD symptoms, in most patients the relief of pain in masseter, temporalis, cervical and TMDs occurred in the 3rd month. Twenty percent of the patients were aware of clenching teeth while awake and reported that this parafunction decreased by the end of 6 months, and 90% reported an improvement in sleep quality as well. CONCLUSION: The use of an OS with a novel adjustment protocol was an effective treatment for TMD sign and symptoms in patients with SB.

INTRODUÇÃO: O bruxismo do sono (BS) é um distúrbio estereotipado de movimento que se caracteriza pela atividade rítmica mastigatória muscular associada com ranger de dentes e apertamento da mandíbula ocasional. OBJETIVOS: O objetivo deste estudo foi determinar o tempo de alívio para desordens temporomandibulares (DTM), cervical e sinais e sintomas otológicos em pacientes com BS tratados com placas oclusais (PO) por um período de 180 dias. MATERIAIS E MÉTODOS: Trinta pacientes, entre 22 e 53 anos, apresentando BS e DTM, incluindo sintomas cervical e otológicos, foram incluídos neste estudo. O protocolo de tratamento do paciente consistiu na utilização da PO com a aplicação de um novo protocolo de ajuste. O período de acompanhamento total foi de 180 dias. O teste t de Student pareado foi utilizado para comparar os efeitos após o tratamento a longo prazo da PO. RESULTADOS: Para todas as variáveis os resultados foram significativos (p < 0,001). Quanto aos sintomas da DTM, na maioria dos pacientes o alívio da dor no masseter, temporal, cervical e DTM ocorreu no terceiro mês. Vinte por cento dos pacientes autorrelataram ranger os dentes enquanto acordado e informaram que essa parafunção diminuiu até o final de 6 meses, 90% dos sujeitos relataram, também, melhora na qualidade do sono. CONCLUSÃO: O uso de uma PO com novo protocolo de ajuste foi um tratamento eficaz para os sinais e sintomas de DTM em pacientes com BS.
Um novo protocolo para ajuste de placa oclusal no tratamento do bruxismo noturno
Keywords: Sleep bruxism; Temporomandibular disorders; Occlusal splints; Pain; Bruxismo do sono; Distúrbios temporomandibulares; Placas oclusais; Dor